2023
DOI: 10.3389/fphar.2023.1098972
|View full text |Cite
|
Sign up to set email alerts
|

The brief overview, antivirus and anti-SARS-CoV-2 activity, quantitative methods, and pharmacokinetics of cepharanthine: a potential small-molecule drug against COVID-19

Binbin Xia,
Li Zheng,
Yali Li
et al.

Abstract: To effectively respond to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), an increasing number of researchers are focusing on the antiviral activity of cepharanthine (CEP), which is a clinically approved drug being used for over 70 years. This review aims to provide a brief overview of CEP and summarize its recent findings in quantitative analysis, pharmacokinetics, therapeutic potential, and mechanism in antiviral and anti-SARS-CoV-2 activity. Given its remarkable capacity against SARS-CoV-2 inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…Treatment of infected cells with CEP decreases viral RNA yield by 2.17- and 1.61-fold, respectively, in both the entry and post entry phases compared with the infected cells without treatment . Another study showed that CEP is effective against SARS-CoV-2 because of its binding potential with NSP multiple subunit complex (nonstructural proteins) . This multisubunit complex of NSP is very much crucial for replication as well as transcription of SARS-CoV-2 (RNA virus) .…”
Section: Mechanistic Basis Of Action Of the Phytochemicals Used For T...mentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of infected cells with CEP decreases viral RNA yield by 2.17- and 1.61-fold, respectively, in both the entry and post entry phases compared with the infected cells without treatment . Another study showed that CEP is effective against SARS-CoV-2 because of its binding potential with NSP multiple subunit complex (nonstructural proteins) . This multisubunit complex of NSP is very much crucial for replication as well as transcription of SARS-CoV-2 (RNA virus) .…”
Section: Mechanistic Basis Of Action Of the Phytochemicals Used For T...mentioning
confidence: 99%
“…70 Another study showed that CEP is effective against SARS-CoV-2 because of its binding potential with NSP multiple subunit complex (nonstructural proteins). 73 This multisubunit complex of NSP is very much crucial for replication as well as transcription of SARS-CoV-2 (RNA virus). 74 Binding of CEP to the NSP machinery blocks the formation of the relevant proteins synthesized by SARS-CoV-2.…”
Section: ■ Mechanistic Basis Of Action Of the Phytochemicals Used For...mentioning
confidence: 99%